The Relationship Between Late Devonian Environmental Evolution and Organic Matter Enrichment - Ma Yingying (E3S Web of Conferences)
This study investigates the interplay between environmental evolution and organic matter (OM) accumulation during the Late Devonian, with a focus on the Frasnian-Famennian (F-F) transition in the Lengshuijiang section, South China. By analyzing geochemical proxies such as Total Organic Carbon (TOC), Phosphorus/Aluminum (P/Al) ratios, Chemical Index of Alteration (CIA), and Co/Ni ratios, we aim to elucidate the factors that controlled OM enrichment during this period. Our findings suggest that the processes driving OM accumulation, including primary productivity and preservation mechanisms, were closely linked to significant environmental changes. The data reveal that periods of high TOC coincided with anoxic or euxinic conditions, driven by global sea-level changes and oceanic stagnation, contributing to increased environmental stress and the F-F mass extinction. Additionally, fluctuations in CIA values indicate alternating warm and humid to cooler, more arid climatic phases, which likely exacerbated environmental stress and disrupted marine ecosystems. This research highlights the interconnectedness of climate, ocean chemistry, and biological evolution during periods of significant environmental upheaval, offering valuable insights into the processes that drove one of Earth's most profound biotic crises.